Acoustic Emission Characteristics under Cyclic Loadings: On the developmemlt of a monitoring system for structures by acoustic emission (II) - KUWABARA, Takao; KOYAMA, Shuhei; NAKAYA, Mitsuo (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1984)
It is considered that most structures are always subjected to some cyclic loadings: moving a load, earthquakes or other types of loads. So report (II) describes the Acoustic Emission characteristics under various cyclic loading conditions to find out some important conditions so as to construct a proper monitoring system for structures. In this report, the fundamental problems of A. E. parameters under cyclic loadings are investigated looking a cyclic loading from two points of view:(1) how to estimate the pre-loading value; and (2) how to estimate whether materials are stable or not. The investigation provided the following results: (1) As for the first point, it can be said that we are able to estimate the pre-loading value in almost all cases with relatively good accuracy from the change of the A. E. count rate or total count. However, in some cases, it is difficult to discover the values, because of some bad material conditions or preloadings conditions. (2) As for the second point, it can be said that from the changes in the count rate and total count after being subjected to cyclic loadings, the stability of the materials can be determined; that is, when the change is decreasing little by little, materials will be stable, and if the change occurs abruptly the material will be unstable. From the above results, we have considered these conditions which will allow for a more effective monitoring system.